Assessment of radioactivity in the soil samples from Imphal city, India, and its radiological implication - B Arunkumar Sharma; Nabadwip Sarangthem Singh; Priya Thiyam Devi; Hirakendu Basu; Sudeshna Saha; R K Singhal (Radiation Protection and Environment, 2017)
The radioactivity concentration and the natural gamma absorbed dose rates of the terrestrial radionuclides (226Ra, 232Th, and 40K) have been determined in soil samples collected from twenty different locations of Imphal city, India, using high-purity germanium detector. The range of activity concentration of 226Ra, 232Th, and 40K in the soil from the studied areas varies from 30.3 Bq/kg (Phayeng) to 155.5 Bq/kg (Lamphel), 21.2 Bq/kg (Yairipok) to 257.1 Bq/kg (Lamphel), and 287.4 Bq/kg (Uchiwa) to 2209.3 Bq/kg (Changangei) with overall mean values of 94.1 Bq/kg, 146.5 Bq/kg and 1222.9 Bq/kg, respectively. The absorbed dose rate and annual effective outdoor dose in the study area range from 61.0 nGyh−1 and 0.4 mSv (Laphupat Tera) to 294.4 nGyh−1 and 1.1 mSv (Lamphel) with an average value of 182.9 nGyh−1 and 1.1 mSv. The external hazard index ranged from 0.4 to 1.8 with an average of 1.1. It was significant in 12 locations as it exceeded unity.